Derrida: guide for the perplexed - "Wolfreys, Julian" (London, 2008)
Continuum's Guides for the Perplexed are clear, concise and accessible introductions to thinkers, writers and subjects that students and readers can find especially challenging. Concentrating specifically on what it is that makes the subject difficult to grasp, these books explain and explore key themes and ideas, guiding the reader towards a thorough understanding of demanding material. Jacques Derrida is one of the most important thinkers of the twentieth century. His writings, his lectures and his involvement in a number of political causes have transformed the way in which literature and cultural studies is taught yet his work is often met with incomprehension, hostility and fear. This guide provides students with a clear, unintimidating introduction to Derrida, the key concepts and ideas associated with his work and the major subjects he addresses. Without assuming any prior knowledge of Derrida's work or literary theory, the guide introduces Derrida's ideas, work, reception and his wider philosophical and critical influence. Throughout, Wolfreys refers to literature and film examples, grounding discussion of theoretical concepts in close reading of specific texts.
Keywords: "Derrida, Jacques-Biography"